2021
DOI: 10.3389/fgeed.2021.604371
|View full text |Cite
|
Sign up to set email alerts
|

Baboon Envelope Pseudotyped “Nanoblades” Carrying Cas9/gRNA Complexes Allow Efficient Genome Editing in Human T, B, and CD34+ Cells and Knock-in of AAV6-Encoded Donor DNA in CD34+ Cells

Abstract: Programmable nucleases have enabled rapid and accessible genome engineering in eukaryotic cells and living organisms. However, their delivery into human blood cells can be challenging. Here, we have utilized “nanoblades,” a new technology that delivers a genomic cleaving agent into cells. These are modified murine leukemia virus (MLV) or HIV-derived virus-like particle (VLP), in which the viral structural protein Gag has been fused to Cas9. These VLPs are thus loaded with Cas9 protein complexed with the guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 111 publications
(162 reference statements)
1
32
0
Order By: Relevance
“…Another advantage of the nanoblades is that we provide Cas9 as a protein. The CRISPR/Cas9 gRNA complexes, so-called RNPs, contained in the VLPs are only transiently present once delivered into the targeted cell (Gutierrez-Guerrero et al, 2021). The fact that Cas9 is present in the cell for a limited time should decrease the number of cuts in off-target sites as shown previously (Mangeot et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage of the nanoblades is that we provide Cas9 as a protein. The CRISPR/Cas9 gRNA complexes, so-called RNPs, contained in the VLPs are only transiently present once delivered into the targeted cell (Gutierrez-Guerrero et al, 2021). The fact that Cas9 is present in the cell for a limited time should decrease the number of cuts in off-target sites as shown previously (Mangeot et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…We have also demonstrated for the KO of two different genes (AR and CFTR) that we can multiplex the nanoblades with two gRNA directed against different target sequences of the same gene. Previously, it was demonstrated that nanoblades can be loaded with multiple gRNAs, even with up to 4 different gRNAs (Gutierrez-Guerrero et al, 2021;Mangeot et al, 2019b). Therefore nanoblades might pave the way to study tumorigenesis in gastrointestinal malignancies (Jefremow et al, 2021) (A) Human rectal eGFP expressing organoids 14 days after treatment or not with anti-GFP nanoblades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The system, commonly known as Nanoblade, is suitable for both in vitro and in vivo manipulations, providing high gene editing efficacy and precision in a cost-effective way. Although they have yet to be applied to NK cells, nanoblades have shown promising results in genome editing of human T, B and CD34 + cells ( 104 ).…”
Section: Genetic Manipulation Of Nk Cellsmentioning
confidence: 99%
“…Finally, problems intimately related to programmable nuclease technology, off-target effects, chromosomal rearrangements, and low levels of HDR in primary cells should be resolved in the future to make gene-editing therapies in humans safer and more efficient. Recent advances in the field of CRISPR/Cas RNP delivery using different viral nanoparticle systems such as Nanoblades ( Mangeot et al., 2019 ; Gutierrez-Guerrero et al., 2021 ), NanoMEDIC ( Gee et al., 2020 ), HIV Gag-Cas9 cleavable fusion ( Hamilton et al., 2021 ), gesicles ( Campbell et al., 2019 ) or Vpr-mediated nuclease encapsidation ( Indikova and Indik, 2020 ) look very promising as provide high efficiency, low toxicity, and reduced off-targeting during editing of clinically relevant types of primary cells. Additionally, pseudotyping viral nanoparticles enables delivery of CRISPR/Cas complexes to specific cell types as was shown by using HIV Env for delivery of β-2 microglobulin gene KO into CD4 lymphocytes ( Hamilton et al., 2021 ).…”
Section: Perspectives In Crispr/cas Anti-hiv Therapy and Concluding R...mentioning
confidence: 99%